Maternal Sepsis: Presentation, Course, Treatment, and Outcomes. Issue 3 (May 2021) - Sundin, Courtney Stanley; Rigg, Kendall; Ellis, Kathleen Kistner
Abstract: Purpose: The current adult definition of sepsis and septic shock, as developed in 1992, does not adequately define sepsis in the pregnant and peripartum women due to the alteration of sepsis presentation in the maternal population. The purpose of this study was to determine potential causative factors for sepsis with the aim of prevention and reducing morbidity and mortality. Study Design and Methods: A descriptive observational design via a retrospective medical record review was used with a convenience sample of 22 women who were identified after admission as having sepsis. The setting was the labor and delivery unit of a large urban hospital in Fort Worth, Texas, with over 5, 000 births per year. Results: The most common diagnoses related to maternal sepsis included urinary tract infections, endometritis, chorioamnionitis, and wound infections. Main causative agents identified were predominantly Escherichia coli ( E. coli ), followed by group B streptococcus (GBS), and group A streptococcus (group A strep). The most prevalent presenting symptom was hypothermia or hyperthermia, followed by tachycardia. Primary laboratory results included above and below normal white blood cell count and elevated lactate levels. Sixty-four percent of patients diagnosed with sepsis were readmitted postpartum and 41% gave birth via cesarean. Clinical Implications: Findings are applicable for nursing care and maternal sepsis protocol development. Early identification of mothers at risk for maternal sepsis and tool development for early diagnosis would be beneficial to support the ongoing work on decreasing maternal morbidity and mortality that have a devastating effect on women, their families, and their health care team. Early warning signs of sepsis can be shared by nurses with new mothers and their families as part of routine postpartum discharge teaching so they know when to call their primary health care provider and when to seek care in person. Abstract : Maternal sepsis is the second leading cause of mortality in obstetric patients and is the reason for at least five percent of maternal intensive care unit admissions in the United States. In this study, nurses evaluated all cases of maternal sepsis in their facility over a five-year period to identify presenting symptoms, vital signs, laboratory data, causative organisms, their clinical course and outcomes for the mother and baby. Using these data, nurses can have a better understanding of early and ongoing signs of maternal sepsis and work with the other members of the perinatal team to promote safe maternity care.